The Implementation of Nonprofit Principles toward Foundation Property Management - Desi Subiyanto; Albertus Sentot Sudarwanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Foundation as a legal entity means that foundation as a legal subject has a property that is separated by civil law so that the foundation property is useful to achieve the goals and objectives of the foundation and not for profit. The nonprofit principle means that the existing capital is not processed for profit, but rather activities that benefit the community. Foundation property, whether in the form of money, goods or other properties obtained by a foundation under the Foundation Law, is prohibited from being transferred or distributed directly in the form of salaries, wages, or honoraria or other forms that can be valued in cash with Governing Board, Executive Board, and Supervisory Board. The implementation of the foundation’s principles in managing the foundation property must be adjusted to the condition of the foundation set out in the Statutes and Bylaws based on the foundation's principles which are Transparency, Accountability, and Publicity.